Estimating sources and sinks of malaria parasites in Madagascar - Felana Angella Ihantamalala; Vincent Herbreteau; Feno M. J. Rakotoarimanana; Jean Marius Rakotondramanga; Simon Cauchemez; Bienvenue Rahoilijaona; Gwenaëlle Pennober; Caroline O. Buckee; Christophe Rogier; C. J. E. Metcalf; Amy Wesolowski (Nature Communications, 2018)
Understanding the source of malaria outbreaks in low-transmission areas is important for controlling the disease. Here, the authors use mobile phone data to map malaria transmission in Madagascar, and are able to show that primary sources of infection in the capital city are found along populated coastal areas.